(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to evaluate the activities and evaluation questions implied in the content of the computer textbook for the fifth preparatory grade according to the creative thinking and developing suggestions through answering the following question: what is the percentage of creative thinking skills in the content of the computer textbook for the fifth Preparatory grade students issued by the Iraqi Ministry of Education/ Directorate General of the curriculum in the academic year (2019-2020)? The researchers followed the descriptive-analytical approach. The research community was determined by the content of the computer textbook for the fifth preparatory grade. As for the research sample, it was limited to all activities and evaluation questions implied in the textbook. To design the content analysis tool, the researcher depended on the creative thinking skills, as well as adopted the unity of the explicit idea in the analysis process. The results showed that the percentages of availability of creative thinking skills (fluency, flexibility, originality, elaboration, and sensitivity to problems) in the activities and evaluation questions implied in the content of the computer textbook are (63.27%, 14.29%, zero, 10.20 %, 12.24%) respectively. The researcher suggested developing the aforementioned skills.